Contribution of deep-earth fluids to the geothermal system: A case study in the Arxan volcanic region, northeastern China - Cui, Yueju; Sun, Fengxia; Liu, Lei; Xie, Chao; Li, Jing; Chen, Zhi; Li, Ying; Du, Jianguo (Frontiers in Earth Science, 2023)
Investigations of the hot spring water and gas in the volcanic region are involved in assessing geothermal resources and understanding groundwater circulation, volcano, and earthquake activities. The origins of water and gas of the hot springs, lakes, rivers, and rain in the Arxan volcanic region (AVR), northeastern (NE) China, were investigated by conducting a field survey and geochemical analysis. The low electrical conductivity (40–835 μS/cm) and low total dissolved solids (TDS, 23.83–540.00 mg/L) of the water samples indicate that they are fresh water. δ18O and δD values of the water samples range from −4.1% to −16.0% and from −61.3% to −119.9%, respectively. Enrichment of heavy isotopes in the rainwater and the crater lake waters was caused by evaporation. The component H2O of the water samples predominantly originated from the meteoric water, with less than 1 vol% contributed by deep-earth fluids. Ions in the rain sample were predominantly derived from sea salt and continental aerosol. Ions in the surface water samples had multiple origins (mineral dissolution, atmospheric, and anthropogenic sources). While the ions in the hot spring water were predominantly derived from both the dissolution of rocks and deep-earth fluids, the latter contributed 73%–87% of Cl− and 86%–99% of Na+ to the hot spring waters. Gases from the hot springs were composed of more than 95% N2 and less than 5% O2 and Ar, with 3He/4He ratios of 0.14–1.17 RA (RA=1.4×10−6). Excess N2, Ar, He, and CO2 of the hot springs were mainly derived from both the crust and upper mantle. About 3%–23% of the total He in the bubbling gases from the crater lake waters and hot springs is derived from the mantle, implying a supplement of heat energy from the mantle to the geothermal systems. Significantly, about 12% of the He dissolved in the Budonghe water is derived from the mantle, indicating that plenty of mantle-derived heat transported by deep-earth fluids keeps the river water from freezing. Our results indicate that Cl and Na ions and 3He/4He ratio are the feasible geochemical indicators for source partitioning of geothermal fluids.